Scale Space and Variational Methods in Computer Vision c - Bruckstein, Alfred M.; Haar Romeny, Bart M.; Bronstein, Alexander M.; Bronstein, Michael M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the Third International Conference on Scale Space Methods and Variational Methods in Computer Vision, SSVM 2011, held in Ein-Gedi, Israel in May/June 2011. The 24 revised full papers presented together with 44 poster papers were carefully reviewed and selected from 78 submissions. The papers are organized in topical sections on denoising and enhancement, segmentation, image representation and invariants, shape analysis, and optical flow.
Keywords: Computer science; Computer software; Data mining; Computer graphics; Computer vision; Optical pattern recognition; Computer Science; Image Processing and Computer Vision; Computer Graphics; Pattern Recognition; Algorithm Analysis and Problem Complexity; Data Mining and Knowledge Discovery; Computation by Abstract Devices